Evaluation of estrus expression of Creole sheep submitted to hormonal protocol outside the breeding season (Research, Society and Development, 2022)
Sheep farming represents an important segment in Rio Grande do Sul's livestock, based on the production of meat, wool and milk. The production of sheep's milk is an activity that still has little expression, despite having potential as a source of daily income and value addition through the production of derivatives. Ewes due to higher milk production, generally high nutritional requirements, larger size and potential presentation. In this context, Creole sheep are promising for this activity, as they are adapted to exclusively pastoral systems. The occurrence of deliveries concentrated in only one time of the year can make the activity unfeasible, since the dairy activity requires staggered production. In this way, the search for alternatives that allow reproduction at different times of the year is of paramount importance to increase herd productivity. This study was carried out in an exploratory way, evaluating the reproductive activity of 21 pluriparous Creole sheep, aged between four and five years, from September to October 2020 (outside the conventional season), in the municipality of Santana do Livramento, Rio Grande do Sul (RS), coordinates 30°48'41"S and 55°28'05"W. The experiment was conducted using a hormonal protocol with the application of a single intramuscular dose of prostaglandin (2 mL). Immediately after application, the females were submitted for five days to a mating period. The moment of estrus was identified by marking the females with the marker ink located in the sternum region of the rams. Ewes showed 38% (8/21) of estrus expression rate. The result showed that the hormonal protocol adopted allowed the expression of estrus outside the natural period.